THE IMPACT OF ONLINE LEARNING ON MATHEMATICS LEARNING OUTCOMES OF CLASS II STUDENTS OF SD NEGERI 191320 RAYA TONGAH - Samosir, Alexander; O. Brusa, Jorge; Aulia Nanda, Ficha; Sihombing, Chintani; Karo Karo, Romaida (International Conference on Health Science, Green Economics, Educational Review and Technology, 2020)
This study aims to describe the impact information in online learning on students mathematics learning outcomes in the teaching and learning process at home due to the presence of COVID-19. This research uses descriptive qualitative research. The population drawn from the researcher, was all students of class II SD Negeri 091320 Raya tongah Pematang raya. As for being the samples of this study, namely the parents of students and teachers of class II SD Negeri 091320 Raya Tongah, totaling 25 people, namely 12 students, 12 parents and 1 class II teacher. Data collection techniques in this research use documentation, interviews, observations, which are looking for data on relevant matters from various kinds in the library such as documents, books, magazines, news. The results of the analysis of the research data obtained show that the impact experienced by students, teachers and parents in online teaching and learning activities is that students' math scores have increased, the impact felt by parents and teachers on mastery of technology is still lacking, additional internet quota costs, employment Additional for parents in assisting children in learning, communication and socialization between students, teachers and parents is reduced.